2014
DOI: 10.1136/jech-2014-204783
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and childhood wheezing disorders: a systematic review and meta-analysis

Abstract: Abstract:BACKGROUND: Previous observational studies have claimed that birthweight and childhood

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 81 publications
5
36
3
1
Order By: Relevance
“…Epidemiological evidence suggests opposing effects of restricted growth before birth on asthma (increased risks) and on other allergic diseases (decreased risks) [116,117,118,119,120,121,122,123,124,125] (online suppl. table 1).…”
Section: Perinatal Exposuresmentioning
confidence: 99%
“…Epidemiological evidence suggests opposing effects of restricted growth before birth on asthma (increased risks) and on other allergic diseases (decreased risks) [116,117,118,119,120,121,122,123,124,125] (online suppl. table 1).…”
Section: Perinatal Exposuresmentioning
confidence: 99%
“…2 While 77 allergic constitution, sensitization to allergens [3][4][5] and/or familial history of allergic disease 6 are 78 recognized risk factors for asthma, studies also suggest that maternal vitamin D status during 79 pregnancy may be associated with the risk of asthma in childhood. 7,8 To date, some birth cohort 80 studies have shown that vitamin D status may play an important role in the development of fetal 81 lungs. [9][10][11] Also, epidemiologic studies have suggested that maternal vitamin D intake 12, 13 as well 82 as vitamin D levels in blood [14][15][16] were inversely associated with respiratory tract infections and 83 other wheezing illnesses, presumably because of its multiple immune effects including induction 84 of antibacterial responses and modulation of T-lymphocytes to suppress inflammation.…”
mentioning
confidence: 99%
“…Although effects of LBW on asthma are likely confounded by gestational age, and preterm birth is also a risk factor for asthma, the increased risk of asthma is also apparent in children born small for gestational age (SGA, birth weight <10 th percentile, OR 1.18) as well as LBW (den Dekker et al 2016). Unlike allergies, these meta-analyses suggest that high birth weight does not affect risk of asthma (Mebrahtu et al 2015).…”
Section: Evidence For Iugr As a Protective Factor From Human Cohortsmentioning
confidence: 80%
“…Using an absolute birth weight criterion of 2.5 kg to define LBW, the incidence of wheezing disorders (predominantly asthma), in childhood and adolescence was 60% higher in LBW than non-LBW in a recent meta-analysis of >1.7 million participants in 37 studies (Mebrahtu et al 2015). Consistent with this, a recent meta-analysis of data from nearly 25,000 individuals in 24 European birth cohorts identified a 32% greater risk of asthma in LBW (< 2.5 kg) individuals compared to all others (den Dekker et al 2016).…”
Section: Evidence For Iugr As a Protective Factor From Human Cohortsmentioning
confidence: 99%